Bigger cakes with less ingredients? A comparison of material use of the world economy - Frank Pothen; Michael Schymura (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
The amount of materials used worldwide in production and consumption increased by 56 per cent from 1995 to 2008. Using an index decomposition analysis based on the logarithmic mean divisia index, we investigate the drivers of material use, both on a global and a country scale. We exploit a panel dataset of 40 countries, accounting for 75 per cent of worldwide material extraction and 88 per cent of GDP, from 1995 to 2008. The results show that economic growth and structural change towards material-intensive countries explain most of the growth in global material use. Slight gains in material efficiency and falling importance of material-intensive sectors have decelerating effects. The country-level analysis reveals substantial heterogeneity. Some nations exhibit stable or falling material use, while it increases notably in most countries. Improving material efficiency is able to dampen growth of material use in important industrializing nations like China or India.
Keywords: Q0; Q40; Q42; Q48; 330; Material use; Index decomposition analysis; Economic growth